KTaO3—The New Kid on the Spintronics Block. Issue 9 (18th January 2022) - Gupta, Anshu; Silotia, Harsha; Kumari, Anamika; Dumen, Manish; Goyal, Saveena; Tomar, Ruchi; Wadehra, Neha; Ayyub, Pushan; Chakraverty, Suvankar
Abstract: Long after the heady days of high‐temperature superconductivity, the oxides came back into the limelight in 2004 with the discovery of the 2D electron gas (2DEG) in SrTiO3 (STO) and several heterostructures based on it. Not only do these materials exhibit interesting physics, but they have also opened up new vistas in oxide electronics and spintronics. However, much of the attention has recently shifted to KTaO3 (KTO), a material with all the "good" properties of STO (simple cubic structure, high mobility, etc.) but with the additional advantage of a much larger spin‐orbit coupling. In this state‐of‐the‐art review of the fascinating world of KTO, it is attempted to cover the remarkable progress made, particularly in the last five years. Certain unsolved issues are also indicated, while suggesting future research directions as well as potential applications. The range of physical phenomena associated with the 2DEG trapped at the interfaces of KTO‐based heterostructures include spin polarization, superconductivity, quantum oscillations in the magnetoresistance, spin‐polarized electron transport, persistent photocurrent, Rashba effect, topological Hall effect, and inverse Edelstein Effect. It is aimed to discuss, on a single platform, the various fabrication techniques, the exciting physical properties and future application possibilities of this family of materials. Abstract : If a truly multifunctional material with a large spin‐orbit coupling is looked for, it would be hard to beat KTaO3 (KTO). The 2D electron gas housed by KTO‐based thin films and heterostructures exhibits spin‐polarization, ferroelectricity, superconductivity, persistent photocurrent, etc., and provides a platform to realize exotic relativistic quantum particles. Read this state‐of‐the‐art review for all the fascinating details.